IDENTIFIKASI SENYAWA KIMIA DAN PENELUSURAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOLIK DAUN TUMBUHAN TEROMPET UNGU - Eva Monica (Universitas Wahid Hasyim Semarang, 2017)
ABSTRACT Petunia (Ruellia brittoniana Leonard) is a wild plant species belonging to the Acanthaceae family. This study aimed to identify the content of ethanolic extract of petunia leaf. A total of 185 grams of petunia leave powder were macerated with ethanol resulting 17.5 grams of ethanolic extract. Chemical identification was performed by using reagents. The test using reagents showed that the extract contains tertiary alkaloid, polyphenol, saponin, and essential oil. The antioxidant activity of the extract was recorded by using DPPH assay with the value of ES54 was 53,39 µg/mL. Keywords: Ruellia brittoniana, Acanthaceae, extract, antioxidant.